Analisis Yuridis Wanprestasi dalam Perjanjian Kerja serta Perlindungan Hukum bagi Para Pihak - Cici Marliani; Deva Nur Fateha; Devia Octi Pertiwi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. Employment agreements are the main foundation in labor relations, binding workers and employers to mutually fulfill rights and obligations. However, in practice, breach of contract often occurs, either by workers or employers. This study aims to analyze the forms of breach of contract in employment agreements, their legal consequences, and the legal protection available to the disadvantaged parties. The research method used is normative juridical with statutory, conceptual, and case approaches. Primary legal materials include the Civil Code, Law No. 13 of 2003 on Manpower, and Law No. 2 of 2004 on Settlement of Industrial Relations Disputes. The results show that breaches committed by employers are easier to prove and may result in administrative to criminal sanctions, while breaches committed by workers require a high standard of proof and rarely lead to termination of employment. Preventive legal protection through standardization of employment agreement content and repressive protection through industrial relations dispute settlement mechanisms have been comprehensively regulated, but implementation still faces obstacles such as lengthy resolution processes and disparities in court decisions. Legal gaps are also found in the protection of digital platform workers who do not have written employment agreements. This study recommends the issuance of implementing regulations categorizing the severity levels of worker violations and revising labor laws to accommodate non-standard workers in the digital economy era.